RANCANGAN SISTEM PENDATAAN WARGA UNTUK ANGGOTA DASAWISMA BERBASIS WEB - Mulia Rahmayu - Universitas Nusa Mandiri; Rosi Kusuma Serli - Universitas Nusa Mandiri; Doni Akhmad Fahruddin - Universitas Bina Sarana Informatika (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2021)
Abstract— The progress of a city can be seen from the compilation of population data for the area and the equal access to facilities and usability obtained by local residents. Currently, the government is consistently trying to develop a community empowerment system starting from small steps, one of which is by developing the Dasawisma system. Dasawisma is a PKK (Community Welfare Development) work program where one or two residents in each Rukun Tetangga are tasked with collecting data on local residents, disseminating information about government programs, conducting inter-member counseling and several other socialization activities. In general, the DKI Jakarta Provincial Government has released the